Environment and behaviour - Sahoo, F. M.; Mishra, P.K.; Pirta, R.S. (Delhi, 1988)
The book enjoys the opportunity of looking into several new dimensions in modern psychological research in human behaviour. Of particular interest is the role played by culture, environment and ecology in regulating and changing behaviour in different types of social psychological contexts. The book analyses adaptation and eco-system. It also looks into the theoretical bases related to cross-cultural psychological research. Finally, touches upon the application of this knowledge in creating a link among Ecology-Environment-Behaviour. A number of new constructs and models appear in this book. This is a guide for researchers and students who value psychology as a social science which aims at bringing well-being to the human race.